TURNOVER INTENTION AMONG LECTURERS IN PRIVATE HIGHER EDUCATION: THE DIRECT IMPACT OF FINANCIAL REWARDS AND MEDIATION OF JOB SATISFACTION AND EFFECTIVE ORGANIZATIONAL COMMITMENT - Kristanti, Farida Titik; Prasetio, Arif Partono; Indiyati, Dian; Madiawati, Putu Nina (Jurnal Aplikasi Manajemen, 2021)
Lecturer responsibilities in presenting learning materials and building students' character is considered very important in preparing future workers/entrepreneur. However, those responsibilities still have not received proper attention in certain institutions and even from the government. If this goes on continuously, it is feared that they will lose well performed individuals. This study aimed to investigate the level of turnover intention from the lecturer in six private universities in Bandung. And the role of financial rewards, job satisfaction, and affective organizational commitment as antecedents. Data collected using an online questionnaire. The numbers of total lecturers in those universities were around 3000. This study used a non-probability sample and distributed 500 questionnaires through the human resources office. And after two months, there are 288 participants which willing to complete the questionnaire. After the more detailed screening, we have 121 responses that met our requirements and can be used in this study. The study found that financial rewards were significantly affected job satisfaction and affective organizational commitment. But it was not significantly affected turnover intention. Partially, job satisfaction and affective commitment have not mediated the relationship between financial rewards and turnover intention. But, simultaneously, both variables have significantly mediated the relationship. These results give new understanding to the managers in the educational organization regarding maintaining the turnover level of their lecturers. In the future, studies can be conducted to cover lecturers from other cities in Indonesia.